PENGARUH MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) TERHADAP MOTIVASI BELAJAR DAN HASIL BELAJAR EKONOMI KELAS XI SMA NEGERI 3 MEDAN - Elsadai Ria Veronika Situmorang; Revita Yuni (Smart Education, 2026)
Abstract: The problem addressed in this study is the low level of students learning motivation and economics learning outcomes, as indicated by the lack of active student participation in the learning process and the suboptimal achievement of learning outcames. One effort that can be made to address this issue is the implementation of the TGT learning model, which incorporates group collaboration, academic games, and competition to enhance student engagement in the learning process. This study aimed to determine the effect of the TGT learning model on the learning motivation and economics learning outcomes of eleventh-grade students at SMA Negeri 3 Medan, both partially and simultaneously. This study employed a quantitative approach with a quasi-experimental research design. The population consisted of all eleventh-grade students of SMA Negeri 3 Medan in the 2025/2026 academic year. The sample comprised Class XI-8 as the control group and Class XI-9 as the experimental group, selected using a purposive sampling technique. Data were collected through learning motivation observation sheets and learning achievement tests. Data analysis was conducted using descriptive statistics, normality tests, homogeneity tests, Independent Samples t-Tests, N-Gain tests, and Multivariate Analysis of Variance (MANOVA). The results showed tat the average learning motivation score of the experimental class increased from 29,53 on the pretest to 37,83 on the posttest, while the control class increased from 29,28 to 33,50. The result of the Independent Sample t-Test indicated that the TGT learning model had a significant effect on student learning motivation with a significance value of 0,000 < 0,05 and a t-value of -6,771. Furthermore, the TGT learning model also had a significant effect on students economics learning outcomes with a significance value of 0,000 < 0,05 and a t-value of -9,349. The N-Gain test results showed that the experimental group achieved an average N-Gain score of 63.31% (moderate category), while the control group achieved an average N-Gain score of 23.58% (low category). Furthermore, the MANOVA test results indicated a Wilks’ Lambda significance value of 0.000 < 0.05 and an F-value of 72.070, meaning that the TGT learning model simultaneously affected students’ learning motivation and economics learning outcomes. Keywords: Team Games Tournament (TGT) Learning Model, Learning Motivation, Economics Learning Outcomes. Abstrak: Permasalahan dalam penelitian ini adalah rendahnya motivasi belajar dan hasil belajar ekonomi siswa yang ditunjukkan melalui kurangnya partisipasi aktif siswa dalam proses pembelajaran serta pencapaian hasil belajar yang belum optimal. Salah satu upaya yang dapat dilakukan untuk mengatasi permasalahan tersebut adalah dengan menerapkan model pembelajaran TGT yang melibatkan aktivitas kerja sama kelompok, permaianan akademik, dan kompetisi yang dapat meningkatkan keterlibatan siswa dalam proses pembelajaran. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran TGT terhadap motivasi belajar dan hasil belajar ekonomi siswa kelas XI SMA Negeri 3 Medan, baik secara parsial maupun secara simultan. Penelitian ini menggunakan metode kuantitatif dengan jenis penelitian quasi eksperimen. Populasi dalam penelitian ini adalah seluruh siswa kelas XI SMA Negeri 3 Medan Tahun Ajaran 2025/2026. Sampel penelitian terdiri atas kelas XI-8 sebagai kelas kontrol dan kelas XI-9 sebagai kelas eksperimen yang ditentukan menggunakan teknik purposive sampling. Teknik pengumpulan data dilakukan melalui lembar observasi motivasi belajar dan tes hasil belajar. Analisis data menggunakan statistik deskriptif, uji normalitas, uji homogenitas, uji Independent Sample t-Test, uji N-Gain dan uji Multivariate Analysis of Variance (MANOVA). Hasil penelitian menunjukkan bahwa rata-rata skor motivasi belajar kelas eksperimen meningkat dari 29,53 pada pretest menjadi 37,83 pada posttest, sedangkan kelas kontrol meningkat dari 29,28 menjadi 33,50. Hasil uji Independent Sample t-Test menunjukkan bahwa model pembelajaran Team Games Tournament (TGT) berpengaruh signifikan terhadap motivasi belajar siswa dengan nilai signifikansi sebesar 0,000 < 0,05 dan nilai thitung sebesar -6,771. Selain itu, model pembelajaran TGT juga berpengaruh signifikan terhadap hasil belajar ekonomi siswa dengan nilai signifikansi sebesar 0,000 < 0,05 dan nilai thitung sebesar -9,349. Hasil uji N-Gain menunjukkan bahwa kelas eksperimen memperoleh rata-rata N-Gain sebesar 63,31% (kategori sedang) sedangkan kelas kontrol memperoleh rata-rata N-Gain sebesar 23,58% (kategori rendah). Selain itu, hasil uji MANOVA menunjukkan nilai Wilks’ Lambda dengan signifikansi sebesar 0,000 < 0,05 dan nilai F sebesar 72,070 yang berarti model pembelajaran TGT berpengaruh secara simultan terhadap motivasi belajar dan hasil belajar ekonomi siswa. Kata kunci: Model Pembelajaran Team Games Tournament (TGT), Motivasi Belajar dan Hasil Belajar Ekonomi